Answer:
Step-by-step explanation:
1. Interchange x and y. We get: x = y^2 - 5
2. Solve for y: y^2 = x + 5, so that y = ±√(x + 5)
Answer: the answer is C
Step-by-step explanation: AP3X
Answer:
48 gallons per hour
Step-by-step explanation:
Step 1:
288 : 6
Step 2:
288 ÷ 6
Answer:
48
Hope This Helps :)
Answer:
![\implies \: 2.6851 \text{ \: ft}](https://tex.z-dn.net/?f=%20%5Cimplies%20%5C%3A%202.6851%20%5Ctext%7B%20%5C%3A%20ft%7D)
![\\](https://tex.z-dn.net/?f=%20%5C%5C%20)
Step-by-step explanation:
![\boxed{\boxed{ \blue\bigstar \red{ \bold{ \: \: math \: \: }} \blue\bigstar}}](https://tex.z-dn.net/?f=%20%20%5Cboxed%7B%5Cboxed%7B%20%20%5Cblue%5Cbigstar%20%20%5Cred%7B%20%5Cbold%7B%20%5C%3A%20%20%5C%3A%20math%20%5C%3A%20%5C%3A%20%20%7D%7D%20%5Cblue%5Cbigstar%7D%7D)
![\pink{\implies = \sqrt{ {36.1}^{2} - {36}^{2}} }](https://tex.z-dn.net/?f=%20%20%5Cpink%7B%5Cimplies%20%3D%20%20%5Csqrt%7B%20%7B36.1%7D%5E%7B2%7D%20-%20%20%20%7B36%7D%5E%7B2%7D%7D%20%20%7D%20)
![\orange{ \implies = \sqrt{1303.21} - 1.296}](https://tex.z-dn.net/?f=%20%5Corange%7B%20%5Cimplies%20%20%3D%20%20%5Csqrt%7B1303.21%7D%20-%201.296%7D)
![\green{ \implies = \sqrt{7.21} }](https://tex.z-dn.net/?f=%20%5Cgreen%7B%20%5Cimplies%20%3D%20%20%5Csqrt%7B7.21%7D%20%7D)
![\red{ \implies = 2.6851 \: \text{ft}}](https://tex.z-dn.net/?f=%20%5Cred%7B%20%5Cimplies%20%3D%202.6851%20%5C%3A%20%20%5Ctext%7Bft%7D%7D)
Answer:
1 a.) 2t – 2
1 b.) –9z + 4
2 a.) –2v + 3
2 b.) –13k – 9
3 a.) 7w − 2
3 b.) 10s
4 a.) 5
4 b.) –3p + 11
5 a.) –29x + 9
b.) 15v – 60x – 2
a.) 25n + 2
b.) –15n
a.) –71x + 4
b.) –15b
Step-by-step explanation:
- <em>NOTE: I am kind of confused about the way this question is formatted, so I tried to answer everything I could decipher.</em>
1 a.) –2t + 5t – 2 – t → 2t – 2
1 b.) –5z + 4 – 4z → –9z + 4
2 a.) 8v + 3 – 10v → –2v + 3
2 b.) –6 – 6k – 3 – 7k → –13k – 9
3 a.) –6 – 3w + 4 + 10w → 7w − 2
3 b.) 9s + s → 10s
4 a.) 6 + 8b – 1 – 8b → 5
4 b.) 1p + 6 + 5 – 4p → –3p + 11
5 a.) 4x – 3x + 9 – 6x 5 → –29x + 9
b.) 9v + 6v – 2 – 10x 6 → 15v – 60x – 2
a.) n + 2 – (–4)n 6 → 25n + 2
b.) 6n – 3n 7 → –15n
a.) –4x – 4x + 4 – 9x 7 → –71x + 4
b.) –9b + (–6)b → –15b